Influence of Particle Geometry Assessed via Image Processing on Broken Sandstone Strength - S. Balideh; T.G. Joseph; M. Curley (Global Journal of Earth Science and Engineering, 2018)
Particle geometry has an impact on the behavior and strength of broken rock, where particle shape characteristics affect the ability of particles to rotate or slide relative to each other. Form, angularity and texture are three independent parameters that describe the geometry of such a particle. In this paper the geometry of crushed Berea sandstone was determined through image processing, where the results showed that form and angularity indices describe the geometry characteristics of broken Berea sandstone better than the other geometry indices. A correction coefficient that has previously been introduced to predict a sieve size distribution from image processing was shown to be a function of form index for the sandstone fragments. Triaxial compression tests were performed on the broken sandstone, showing that confining pressure and void ratio have an impact on broken rock strength. Increasing confining pressure was shown to enhance the strength of broken rock, while void ratio was shown to be inversely related to broken rock strength. Void ratio can also be affected by particle geometry. Increasing particles form index increases the void ratio where particles angularity index and void ratio are inversely related.